Conception and Characteristics of Expert Mathematics Teachers in China - Yang, Xinrong. author. aut Link
XX, 321 p. 25 illus.
Keywords: The superior performance of East Asian students in recent international studies of mathematics achievement has attracted the attention of educators and policy makers worldwide. Xinrong Yang focuses on exploring how an expert mathematics teacher is conceptualized by mathematics educators in China and the characteristics that expert mathematics teachers share. The author adopts a sociocultural theory and a prototypical view of conception in this study of teacher expertise and shows that some of the roles expected to be played by expert mathematics teachers in China, such as being at the same time a researcher, a mentor, an expert in examination, and an exemplary model, are quite different from the roles expected of an expert teacher in Western cultures. In addition, some characteristics of expert mathematics teachers the author identifies are different from those reported in previous studies. Examples include the expert mathematics teachers´ contemporary-constructivist oriented beliefs about mathematics and its learning and teaching, and their ability to teach with flexibility, balance, and coherence. Contents · Conception of Expert Mathematics Teachers · Beliefs and Knowledge of Expert Mathematics Teachers · Classroom Teaching Practice and Sociocultural Influences Target Groups · Researchers, academics and scholars of mathematics and didactics · Teachers The Author Dr. Xinrong Yang works as an associate professor at the Southwest University, Chongqing, P. R. China. The Editor(s) The series Perspektiven der Mathematikdidaktik is edited by Prof. Dr. Gabriele Kaiser, Prof. Dr. Rita Borromeo Ferri, and Prof. Dr. Werner Blum.